Multicompartmental pharmacokinetic evaluation of long‐acting cabotegravir in healthy adults for HIV preexposure prophylaxis. Issue 4 (29th July 2021) - Shaik, Jafar Sadik; Weld, Ethel D.; Edick, Stacey; Fuchs, Edward; Riddler, Sharon; Marzinke, Mark A.; D'Amico, Ronald; Bakshi, Kalpana; Lou, Yu; Hendrix, Craig; Han, Kelong; Ford, Susan L.; et al.
Abstract : Aims: Cabotegravir is an integrase strand transfer inhibitor in clinical development as long‐acting (LA) injectable HIV preexposure prophylaxis. Methods: This phase I study assessed pharmacokinetics of cabotegravir in plasma and anatomical sites associated with sexual HIV‐1 transmission after repeated oral and single intramuscular (IM) LA dosing in healthy adults. Following a 28‐day oral lead‐in period of cabotegravir 30 mg and a washout period of 14–42 days, participants were administered a single ultrasound‐guided gluteal IM cabotegravir LA 600‐mg injection. The study objective was to characterize cabotegravir concentrations in plasma, cervical, vaginal and rectal tissues, and cervicovaginal and rectal fluids and up to Week 12 after IM injection. Results: Nineteen participants enrolled and 16 completed the study through Week 52. Cabotegravir was detected in plasma and all tissues and fluids. Median plasma cabotegravir concentrations exceeded the in vitro protein‐adjusted 90% maximal inhibitory concentration through Week 12. Median tissue‐ and fluid‐to‐plasma cabotegravir concentration ratios across all visits were 0.32 for rectal fluid and 0.08–0.16 for other tissues and fluids. Adjusted R 2 coefficients between cabotegravir concentrations in plasma and cervical, vaginal and rectal tissues were 0.78, 0.79 and 0.90, respectively. Injection‐site reactions were common (88% of participants) and were mostly grade 1 in intensity (82%). Two participants reported 11 non–drug‐related serious adverse events. Conclusion: Concentrations of cabotegravir in tissues and fluids were proportional to plasma over time, with strong correlations between tissue and plasma concentrations. Cabotegravir LA tissue‐to‐plasma ratios may be important for understanding its use as preexposure prophylaxis.